Solubilidade de alguns corretivos em quatro solventes químicos e sua relação com alguns parâmetros do solo - Eure Pereira, Joaquim; Braga, José Mário; Cristo Brumano Pinto, Onofre; Maffia de Oliveira, Laede (Revista Ceres, 2025)
The solubility of leven liming materials (seven limestone, two basic slags and two pure carbonate), was determined using as chemical solvents 0.1 N hydrochloric acid, 1% acetic acid, 1 N ammonium chloride and 0.25 N EDTA.